Development and dosimetric evaluation of radiochromic PCDA vesicle gel dosimeters. (February 2016) - Sun, P.; Fu, Y.C.; Hu, J.; Hao, N.; Huang, W.; Jiang, B.
Abstract: The gel dosimeter has the unique capacity in recording radiation dose distribution in three dimensions (3D), which has the specific advantages in dosimetry measurements where steep dose gradients exist, such as in intensity-modulated radiation therapy (IMRT), brachytherapy and so on. Some 3D dosimeters, such as Fricke gel dosimeters, polymer gel dosimeters, the PRESAGE plastic dosimeters and micelle gel dosimeters have appeared recently. However, there are several disadvantages of these 3D dosimeters limit their application in radiotherapy dose verification. In this study, a novel radiochromic gel dosimeter for 3D dose verification of radiotherapy was developed by dispersing nanovesicles self-assembled by 10, 12-pentacosadiynoic acid (PCDA) into the tissue equivalence gel matrix. The characteristics of radiochromic PCDA vesicle gel dosimeters were evaluated. The results indicate that these radiochromic gel dosimeters have good linear dose response to X-ray irradiation in the dose range of 2–100 Gy. In addition, the radiochromic gel dosimeters breakthrough the limitations of the existing gel dosimeters such as diffusion effect, post-radiation effect, and poor forming ability. The response of the gel dosimeter does not show any dose rate dependence, energy dependence and temperature effect, and there was no obvious difference in the gel response between single and cumulative dose of fractional irradiation. Hence, the radiochromic PCDA vesicle gel dosimeters developed in this study could be generally applied to 3D dose verification in radiotherapy. Highlights: A novel radiochromic gel dosimeter was developed by dispersing PCDA nanovesicles into the tissue equivalence gel matrix. This nanovesicle overcomes the dose image blurring caused by the diffusion of monomer molecules. This nanovesicle limits the polymer chain growth, so as to reduce the post-radiation effect. The gel matrixes possess excellent tissue equivalence and elastic strength, which could be arbitrarily shaped or cut.